Pengaruh Human Relation, Kondisi Fisik Lingkungan dan Organization Based Self-Esteem Terhadap Etos Kerja Serta Dampaknya Pada Kinerja Karyawan BPR Kedung Arto Semarang - Iik Suryati Azizah (Politeknik Bumi Akpelni, 2019)
This research intent to test Subjective implement effectiveness Human Relation, Condition of Environment Physical, Organization Based Self Esteem to job and Performance Ethos. Base former observational result, condition of environment physical constitute molded environment of implemented subjective human squire. Relationship among human contain mean a communication since its character that orientation on behavioral. Therefore, organization righteously has give freedom to fire an employee to get that communication they can collaborate properly in their work. This research is done on BPR Kedung Arto at Semarang. Method that is utilized as method of census via pervading questionnaire of population a number 102 person. Two phase regression analysis is utilized as quantitative analysis. Coefficients arithmetic result determinant totaled point out that 72% changing variable dependent can be worded by independent variables. Meanwhile its rest as big as 28% worded by outdoor other variables model observational. Hypthothesis testing result partially of each step points out to mark sense influence positively and significant of job Ethos to Performance. Hereafter, Human Relation, Condition of Environment Physical and OBSE each have influence positively and significant to job Ethos.